2016
DOI: 10.1093/jxb/erw280
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of salicylic acid delay methyl jasmonate-induced leaf senescence by up-regulating nitric oxide synthase activity

Abstract: In plants, extensive efforts have been devoted to understanding the crosstalk between salicylic acid (SA) and jasmonic acid (JA) signaling in pathogen defenses, but this crosstalk has scarcely been addressed during senescence. In this study, the effect of SA application on methyl jasmonate (MeJA)-induced leaf senescence was assessed. We found that low concentrations of SA (1-50 μM) played a delayed role against the senescence promoted by MeJA. Furthermore, low concentrations of SA enhanced plant antioxidant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 81 publications
1
35
0
Order By: Relevance
“…Evidence supports the interaction of NO with other plant hormones to loral senescence and fruit maturation [157]. Recently, Ji et al [158] demonstrated that SA treatment at low concentrations induced NOA1-dependent NO signaling and activated antioxidant defense to counteract MeJA-induced leaf senescence. NO plays a conceivable role to counteract the ABA-and jasmonate-induced senescence in rice by inhibiting H 2 O 2 accumulation and lipid peroxidation [159].…”
Section: Contrasting Reports Inmentioning
confidence: 83%
“…Evidence supports the interaction of NO with other plant hormones to loral senescence and fruit maturation [157]. Recently, Ji et al [158] demonstrated that SA treatment at low concentrations induced NOA1-dependent NO signaling and activated antioxidant defense to counteract MeJA-induced leaf senescence. NO plays a conceivable role to counteract the ABA-and jasmonate-induced senescence in rice by inhibiting H 2 O 2 accumulation and lipid peroxidation [159].…”
Section: Contrasting Reports Inmentioning
confidence: 83%
“…Our results also suggest that genetic manipulation of RD1 and RD2 genes of the AP2/ERF family may enhance production of secondary metabolites resulting in improved drought stress tolerance (Mawlong et al, 2015). Epigenetic regulation of gene expression (Wang et al, 2016) under abiotic stresses (Kumar and Singh, 2016; Kumar et al, 2017) and signaling cascades (Bernsdorff et al, 2016; Ji et al, 2016) that regulate defense mechanisms remain to be elucidated. The present findings would facilitate unraveling the elicitor induced biochemical and molecular manifestations of drought tolerance in crop plants to improve the yield.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, S ‐acyltransferase‐associated NOA1 activity and the onset of leaf senescence occurred in an age‐dependent manner (Ji et al . ) involving a mechanism that is evolutionarily conserved between dicots and monocots (Zhao et al . ).…”
Section: Discussionmentioning
confidence: 99%